Pregnancy Profile and Infant Outcomes Among HIV Infected Women Who Delivered in Cipto Mangunkusumo Hospital - Junita Indarti; Evy Yunihastuti; Nia Kurniati; Bella Aprilia; Danang T Pamungkas; Ariel T Chiprion; Mega A Ginting; Saiful Rizal; Citra Dewi; Lieke Handayani (Acta Medica Indonesiana, 2020)
Background: HIV infection in pregnancy is a big concern for the future of our nation. The virus can be transmitted to the baby through pregnancy, childbirth and during breastfeeding which rendering to early detection and intervention. The aim of this study was to describe the transmission prevention cascade among our patient. Methods: this was a retrospective cohort study of HIV vertical transmission. The inclusion criteria was pregnant women with HIV infection who have antenatal care in Cipto Mangunkusumo Hospital from January 2013 up to December 2018. Data was retrieved from medical record, HIV registry and laboratory results. The included data were demographic, risk of infection, obstetrical data, mode of delivery, ARV history, laboratory history in mother and infant. Data was presented as descriptive. Results: there was 138 HIV pregnant women included as study subjects. Most women were at 25-29 years old (39.85%), as housewife (41.30%), with history of more than one sexual partners (50.73%). The subjects was mostly multigravida (77.5%), first visit to RSCM in third trimester (98.6%), with history of antenatal care >4 times (48.6%), singleton fetus (99.3%), and delivered by C-section (84.1%). HIV diagnosis was done during pregnancy (73.53%), and already on antiretroviral (ARV) for more than 6 months (50.7%). There was 78% subjects with CD4 (24% subjects with <200 cells/mL) and 84% with viral load data (36% with viral load >200 copies/uL). Around 72.5% infants born with birth weight 2500-3500g. Almost all infant received ARV prophylaxis (97.9%) and formula feeding. PCR HIV was examined on 16 infant on 6 weeks of age and and 13 on 6 month age. There was 1 infant with viral load results >400 copies/ml which immediately refered to Pediatric HIV clinic. Bivariate analysis showed significant correlation between maternal ARV consumption and infant result at birth (P=0.05). Maternal CD4 level was not significantly correlate with neonatal virology status (P=0.12). Conclusion:HIV diagnosis in pregnant women is important, since ARV administration on early pregnancy significantly reduce vertical transmission. ARV prophylaxis protocols is important to prevent HIV infection on infant.